Fostering transformative learning and whole patient care among teaching hospital staff through artistic creation: a qualitative study - Kang-Ju Chou; Ying-Yao Cheng; Wen Cheng; Hsueh-Hua Chuang; Chun-Teng Tsai; Hua-Chang Fang (BMC Medical Education)
Abstract Background The whole person care (WPC) model has become a core objective of medical education. In this model, transformative learning is employed to broaden health-care providers’ (HCPs) perspectives. To explore how artistic creation influences HCPs’ perceptions of the value of WPC, this study examined the content of artworks created by HCPs in teaching hospitals. Methods In this study, using Mezirow’s phases of perspective transformation as a theoretical framework, a retrospective qualitative analysis was conducted to investigate the content of HCPs’ art projects presented at annual WPC-experience-sharing workshops held from 2019 to 2021 at a teaching hospital in Taiwan. A content analysis applying template analysis principles was employed. The data were categorized according to an iteratively refined template until a consensus was reached by the researchers regarding the identified themes and subthemes. Results From 2019 to 2021, 226 art projects were presented in the annual week-long exhibition. Postgraduate-year physicians and other hospital staff created 140 and 86 artworks, respectively. The participants included 127 men and 99 women aged between 22 and 55 years. The researchers identified 4 themes and 12 subthemes of transformational learning concerning the meaning of life and the value of WPC across Mezirow’s phases. The four themes were (1) deep reflection on the meaning of life and death, (2) connection, (3) deepening and valuing health-care professional identity, and (4) reaffirming the motivation to serve. Conclusions Our results align with Mezirow’s phases of TL, with art creation highlighting key phases such as self-examination and critical reflection. Physicians showed greater engagement in these phases than other professionals. The most commonly represented phase focused on connection, while themes related to life and death were less frequent among non-medical participants. Overall, our findings demonstrate how artistic expression facilitated TL among healthcare professionals, allowing them to reflect on their identities, relationships, and professional responsibilities. These cognitive exercises foster active learning, WPC, and promote an awareness of the meaning and value of life in teaching hospitals.